A Novel Germline Pathogenic Variant of RECQL4 Gene in an Iranian Pedigree with Familial Squamous Cell Carcinoma: A Brief Report - Mina Amin; Elaheh Mahmoodi-Khaledi; Sina Narrei; Mehrdad Zeinalian (Iranian Journal of Medical Sciences, 2023)
Squamous cell carcinoma (SCC) is the most common human solid tumor and the leading cause of cancer death. SCC of the breast is a very rare type of cancer that has not been well researched. Early identification of the genetic factors involved can lead to early diagnosis and targeted treatment. The present study was conducted in 2018 at Isfahan University of Medical Sciences (Isfahan, Iran). The proband was a 66-year-old woman with SCC of the breast and a positive family history of cancer. Blood DNA samples were used for whole-exome sequencing to identify germline pathogenic variants. Variant annotation and prioritization were done on variant call format files using bioinformatics software tools. The screened variants were confirmed using the Sanger sequencing method. Co-segregation analysis was performed on the blood DNA samples of the first- and second-degree relatives of the proband to assess the presence of the mutation. A novel germline pathogenic variant was identified in the RECQL4 gene of the family. RECQL4 is a known protein in DNA repair and replication. Considering its effect on other types of SCC, it may play an important role in SCC initiation and progression in the breast.